Paenibacillus Naphthalenovorans Biofilms Interact with and Degrade Naphthalene as Observed using Various Microscopy Techniques - Aliyeva, Saida; Petersen, James N.; Park, Bong-Jae; Abu-Lail, Nehal I. (Journal of Environmental Science and Engineering Technology, 2019)
The role of Paenibacillus naphthalenovorans biofilm formation in degrading a model polycyclic aromatic hydrocarbon (PAH) (naphthalene) was investigated via an array of microscopy techniques. The early stages of biofilm formation near a naphthalene crystal that was deposited on a glass coverslip were assayed qualitatively by growing the biofilms in batch bioreactors using either a rich carbon medium or a medium which contained naphthalene as a lone carbon source. Our results demonstrated that the biofilm selectively grew immediately adjacent to the edge of the PAH crystal, leading to a biofilm that facilitated the PAH degradation. Moreover, because PAH compounds are often found in capillary spaces in the subsurface, quantitative capillary-experiments were executed to evaluate the ability of P. naphthalenovorans biofilms in the degradation of a capillary-bound PAH contaminant. These capillary-experiments demonstrated that a biofilm forms at the pore’s opening, and that, when compared to a diffusion process in a liquid medium, this biofilm substantially increased the rate at which the PAH is cleared from the pore. These results provide an enhanced understanding of the means of biofilm adhesion and development in a presence of the model PAH compound investigated. Moreover, the work presented here demonstrates approaches not used before for monitoring biofilm formation.